Analysis of the Literature on Cervical Spine Fractures in Ankylosing Spinal Disorders. (August 2017) - Hartmann, Sebastian; Tschugg, Anja; Wipplinger, Christoph; Thomé, Claudius
Study Design: Narrative literature review. Objective: The numbers of low-energy cervical fractures seen in patients suffering from ankylosing spondylitis (also known as Bechterew disease) or diffuse idiopathic skeletal hyperostosis (also known as Forestier disease) have greatly increased over recent decades. These fractures tend to be particularly overlooked, leading to delayed diagnosis and secondary neurological deterioration. The aim of the present evaluation was to summarize current knowledge on cervical fractures in patients with ankylosing spinal disorders (ASDs). Methods: The literature was analyzed through an extensive PubMed search focusing on cervical fractures, especially with delayed diagnosis. Results: In ASDs, it was mainly the cervical spine that was found to be affected by fractures. Fifty percent of ASD patients had neurological deficits at admission, with a high probability of secondary deterioration due to an initially missed diagnosis. Multislice high-resolution imaging techniques should be the radiological standard of care if a vertebral fracture is suspected. Nevertheless, many of these spinal fractures are overlooked, leading to feared secondary deterioration of existing unstable fractures. Long posterior instrumentations were found to be the treatment of choice, followed by anterior and combined anterior-posterior instrumentations. Conclusions: Delayed diagnosis of cervical fractures in ASDs contributes to initially misinterpreted clinical symptoms, inadequate imaging techniques, and a lack of knowledge about this disease entity due to its peculiarities. Thorough assessment of the patients' neurological morbidity at admission might reduce the occurrence of the associated fractures. The biomechanical behavior of ASD fractures is completely different from that of non-ASD fractures, so that the treatment strategy for these patients should be at least surgical, in combination with long dorsal instrumentations or combined anterior-posterior approaches.